Higher Education as a Means of Achieving Economic Growth and Development – A Comparative Analysis of Selected EU and former Soviet Union Countries - Maja Grdinić (Central European Public Administration Review)
In the last twenty years, higher education policies have become increasingly important national priorities in both the developed and the developing countries. According to the endogenous growth theory, higher education and thereby accumulation of human capital is considered to be the main driver of economic competitiveness in the growing global economy founded on knowledge. Thus, as education is undoubtedly one of the main drivers of economic growth and development, an increase in the real expenditures for education is found in many countries. All this is especially evident in times of rapid technological changes. The interest of this paper is to show the relationship between GDP and public spending on education by applying the method of panel data analysis on the selected EU Member States and former Soviet Union Countries for the period 2000 – 2011. The results of the analysis showed that public expenditure for education, as well the size of the tertiary educated workforce and the number of researchers have a positive impact on GDP growth.